2007
DOI: 10.1016/j.lfs.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

SLURP-1 and -2 in normal, immortalized and malignant oral keratinocytes

Abstract: The secreted mammalian Ly-6/urokinase plasminogen activator receptor-related proteins (SLURP)-1 and -2 are produced by keratinocytes comprising the mucocutaneous epithelium. They regulate in autocrine and paracrine ways cell growth and differentiation through the nicotinic acetylcholine receptors (nAChRs) expressed on the plasma membrane. Keratinocyte nAChRs are targeted by tobacco-derived carcinogenic nitrosamines 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N'-nitrosonornicotine (NNN) that can in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 13 publications
2
58
1
Order By: Relevance
“…In a previous study, we found that recombinant SLURP-1 and -2 can lessen tumorigenic activities of tobacco-derived nitrosamines [6]. The intact Het-1A cells had decreased SLURP-1 and -2 mRNA levels that further decreased after treatment of cells with carcinogenic nitrosamines.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…In a previous study, we found that recombinant SLURP-1 and -2 can lessen tumorigenic activities of tobacco-derived nitrosamines [6]. The intact Het-1A cells had decreased SLURP-1 and -2 mRNA levels that further decreased after treatment of cells with carcinogenic nitrosamines.…”
Section: Discussionmentioning
confidence: 81%
“…We could not detected either SLURP protein in the 120-fold concentrated supernatants of Het-1A cell cultures, whereas the protein bands corresponding to SLURP-1 and -2 could be visualized in 80-fold concentrated supernatants of cultures of normal keratinocytes. The levels of SLURP-1 and -2 mRNA levels in Het-1A cells decreased further after treatment of cells with NNK [6]. These preliminary results suggested that SLURPs may protect keratinocytes from malignant transformation.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations